Potential mechanism of tea for treating osteoporosis, osteoarthritis, and rheumatoid arthritis - Xie, Xinyu; Fu, Jiehui; Gou, Weiying; Qin, Yifei; Wang, Dingzhen; Huang, Zuer; Wang, Lili; Li, Xihai (Frontiers in Medicine, 2024)
Osteoporosis (OP), osteoarthritis (OA), and rheumatoid arthritis (RA) are common bone and joint diseases with a high incidence and long duration. Thus, these conditions can affect the lives of middle-aged and elderly people. Tea drinking is a traditional lifestyle in China, and the long-term intake of tea and its active ingredients is beneficial to human health. However, the mechanisms of action of tea and its active ingredients against OP, OA, and RA are not completely elucidated. This study aimed to assess the therapeutic role and related mechanisms of tea and its active ingredients in OP, OA, and RA. Moreover, it expanded the potential mechanisms of tea efficacy based on network pharmacology and molecular docking. Results showed that tea has potential anti-COX properties and hormone-like effects. Compared with a single component, different tea components synergize or antagonize each other, thereby resulting in a more evident dual effect. In conclusion, tea has great potential in the medical and healthcare fields. Nevertheless, further research on the composition, proportion, and synergistic mechanism of several tea components should be performed.